TEACHERS’ PERSPECTIVES ON PROMOTING CHILDREN’S PARTICIPATION IN EARLY CHILDHOOD EDUCATION - Delijeva, Gunita; Ozola, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
In democratic society, participation is child’s right from an early age. Within early childhood educational practice, teachers should create diverse and meaningful situations in which children can get experience of how to be part of a group or community. The aim of the study was to examine teachers’ perspectives on promoting children’s participation in early childhood education. A survey of teachers involved in 5- and 6-year old children’s preparation for school was conducted. 2419 teachers representing 741 educational institutions of Latvia participated in the survey. Using a 6-point Likert scale, respondents assessed different statements regarding children’s participation in early childhood education. Teachers’ preparedness to carry out the children’s participation in their educational practice was self-assessed as well. Data were analyzed using descriptive statistics. The analysis of the survey data shows that teachers consider children’s participation a significant component of the educational process. The involvement of children in the discussion of important group issues and their influence on decision-making as well as teachers’ respect of children’s questions during the play-based lesson time was ambiguously assessed. Most teachers declare appropriate self-assessed competences to promote children’s participation in their educational practice.